PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 – 2021 - Destia Cristia Parenta; Fharel M. Hutajulu; Melinda Malau (Buletin Ekonomi, 2023)
Abstract Purpose this research is to find out the impact company sized, company aged and KAP sized on auditorial delays in general industries and chemicals manufacturing companied list on IDX. Period of this research is five years, from 2017 to 2021. This research used secondaries data in form of a series time which covers the variables of company size, companies aged, and also sized of a public account firm using annual data. Data analyst method using is multiple linear regression analyst with descriptive analysis of data including descriptive statistics, classical assumptions including normally test, multicollinearity, heteroscedasticity test, and autocorrelation test then hypothesis tested include F test, t test and coefficient determination test (R2). The following research findings find that audit delay is simultaneously influenced by company size, company age, and the size of the public accounting firm. Furthermore, company size has no partial effect on the length of audits in manufacture company in general and chemical industries list on IDX for period 2017-2021. Company Age partially has a positive and significancy effects on Audit Delay and KAP Sizes partially has a negative and significancy influenced on Audit Delay in manufacture company in general and chemical industries list on Indonesia Stock Exchange for period 2017-2021. Keywords: Audit Delay, Company Size, Company Age, Public Accounting Firm